Gas Analysis Using Raman Spectroscopy Demonstrates the Presence of Intraperitoneal Air (Nitrogen and Oxygen) in a Cohort of Children Undergoing Pediatric Laparoscopic Surgery. (February 2015) - Taylor, Susan P.; Sato, Thomas T.; Balcom, Anthony H.; Groth, Travis; Hoffman, George M.
<x xml:space="preserve">Abstract</x> Clinically significant gas embolism during laparoscopy is a rare but potentially catastrophic event. Case reports suggest that air, in addition to the insufflation gas, may be present. We studied the effects of equipment design and flushing techniques on the composition of gas present under experimental and routine pediatric surgical conditions. Concentrations of nitrogen (N2), oxygen (O2), and carbon dioxide (CO2) were measured by Raman spectroscopy in gas delivered to and retrieved from a mock peritoneum during simulated laparoscopy. We then analyzed the composition of insufflated and recovered gases during elective laparoscopic procedures conducted with CO2-preflushed and unflushed tubing to determine the presence of significant (10%) quantities of air. In vitro, CO2 was not detected at the distal end of insufflator tubing until after delivery of approximately 0.2 L of gas, and N2 persisted until >0.4 L was delivered, with 40% ± 8% (mean ± SD, range 33%–49%) recovered from the mock peritoneum at the termination of initial insufflation. In clinical studies, preflushing reduced the initial concentration of N2 from 78% ± 0.5% to 23% ± 15%, but >10% air was detected in all subsequent samples, regardless of insufflation technique. Laparoscopic equipment and practice routinely permit delivery of air to the insufflated cavity. Purging the equipment with CO2 reduces but does not eliminate air (N2, O2) within the peritoneal cavity during laparoscopy. Thus, when vascular injury occurs, embolized gases will contain variable quantities of N2, O2, and CO2. As the initial insufflation volume diminishes and approaches the volume of the insufflation tubing, which occurs in infants and young pediatric patients, the concentration of N2 will approximate that of room air in an unflushed system. Small insufflation volumes containing high N2 concentrations can contribute to catastrophic air emboli in neonates and small pediatric patients.